Energy-Efficient Wavelength Multiplexers Based on Hydrogenated Amorphous Silicon Resonators - T. Lipka; L. Moldenhauer; J. Muller; H. K. Trieu (IEEE Photonics Journal)
Optical multiplexers are key components of modern data transmission systems that have evolved from long-haul fiber communication applications down to the photonic interconnect level on-chip, which demand high bandwidths and low-power photonic links with small footprint. We present compact, energy-efficient, and high-bandwidth optical add/drop multiplexers that are based on complementary metal–oxide–semiconductor (CMOS) backend-compatible hydrogenated amorphous silicon microring resonators. We study the manufacturing nonuniformity of the as-fabricated devices and analyze the static power consumption that is required to actively align the multiplexers to a 100-GHz grid by using state-of-the-art microheaters. The microring filter banks are in excellent agreement with the design and satisfy a good tradeoff between concurrent properties of high-data-rate capability, low filter loss, high channel isolation, and manufacturing uniformity, which facilitates the operation with low static power consumption. In addition, we demonstrate that it is possible to permanently correct the unavoidable fabrication imperfections and to arrange the individual wavelength channels by a postfabrication trimming method so that the static power is reduced by more than an order of magnitude and allows minimization of these parts of the overall power requirements of such photonic integrated circuits down to record low metrics of a few femtojoules per bit.